Challenges in molecular diagnostic research in cancer nanotechnology. (August 2019) - Caracciolo, Giulio; Vali, Hojatollah; Moore, Anna; Mahmoudi, Morteza
Graphical abstract: Highlights: Introducing the reasons for the existing chasm gap between cancer therapeutic and diagnostic approaches. Drawing the attention of researchers, entrepreneurs, and policy-makers to the importance of diagnostics approaches in lowering the social burden and costs of cancer. Critical information on biomolecular corona should be considered in clinical translation of nanotechnologies. Abstract: Development of robust cancer prevention strategies have the capacity to reduce the need for therapeutic products, relieve patient's suffering and alleviate the crushing financial burden for both patients and their families. Therefore, the obvious choice that would benefit the largest number of people is to realign the importance and prioritization of diagnostics alongside therapeutics. However, entrepreneurs and policy-makers are more inclined to invest in manufacturers of therapeutics, which produce much higher revenues compared to diagnostics companies. The central aim of this opinion article is i) to identify the reasons for this chasm gap between therapeutic and diagnostic approaches in cancer research; and ii) to draw the attention of researchers, entrepreneurs, and policy-makers to the importance and potential promises of diagnostic approaches in lowering the social burden and cost of cancer.